Young adults’ acceptance of shared autonomous vehicles in an urban-university setting - Etminani-Ghasrodashti, Roya; Patel, Ronik Ketankumar; Pamidimukkala, Apurva; Kermanshachi, Sharareh; Rosenberger, Jay Michael; Foss, Ann (Frontiers in Built Environment, 2025)
IntroductionThis study focuses on a shared autonomous vehicle (SAV) demonstration implemented in Downtown Arlington and university campus to provide a representation of individuals’ experiences with autonomous vehicles. We aim to understand how younger, better-educated individuals and students usually assumed to be early adopters of new technologies would accept SAVs.MethodsThis study utilized the survey data to investigate the factors that affect the individual’s inclination to use and adopt the SAVs. Using a structural equation model (SEM), this study tested the effects of factors shaping individuals’ acceptance of SAVs, including attitudes and travel modes.Results and discussionThe study findings revealed that younger individuals and individuals with lower income are more prone to adopt SAVs. The findings demonstrated that favorable perceptions regarding SAVs markedly affect individuals’ willingness to utilize the service. Car users, those with more dependency on cars and fewer ridesharing experiences, are less interested in riding in SAVs, which portends that integrating SAVs and on-demand rideshare services will enhance the accessibility of individuals who already take advantage of ridesharing opportunities. These findings offer a clearer understanding of the potential market for SAV service providers and deepen knowledge about SAV adoption among young people who are more receptive to new technologies.